The Implementation of Jigsaw Type Cooperative Learning Model to Improve Student Learning Outcomes in Class VI Indonesian Language Subjects - Sari, Desi Anita; Mahmudah, Masrurotul; Aisyah, Nurul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to describe the application of the jigsaw type cooperative learning model to improve the learning outcomes of Indonesian language of grade VI students of SDN 3 Bumi Nabung Baru. The approach used in this study is a descriptive qualitative research method. The subjects of the study were grade VI teachers and grade VI students with a total of 12 students. The techniques used in data collection were carried out by means of observation, interviews, and documentation. The results of the study showed that the application of the Jigsaw type cooperative learning model in Indonesian language learning can improve student learning outcomes. Student learning outcomes in the material Analyzing intrinsic elements of narrative text using the jigsaw type cooperative learning model can be seen from Three Domains, namely the cognitive domain, the affective domain and the psychomotor domain. The Cognitive Domain is a person's behavior that emphasizes intellectual aspects such as knowledge and thinking skills such as developing students' social skills, developing students' potential, developing students' abilities in understanding the material. The affective domain is a domain related to interests, attitudes, values and behaviors such as attitudes of mutual respect for opinions, increasing attitudes of cooperation, increasing attitudes of responsibility. Psychomotor domain is an aspect related to skills or the ability to act after students receive learning experiences such as presenting in front of the class to convey the results of discussions. Thus, the jigsaw type cooperative learning model has proven to be an effective alternative to improve the quality of learning in class VI of SDN 3 Bumi Nabung Baru